Carbon Dioxide (CO2) laser cut quality of acrylic with different power levels - Mohd Aiman Shah, Abdullah (2008)
Laser is widely applied in today’s industry. Laser is widely used in industry for cutting and boring metals and other materials, in medicine for surgery, and in communications, scientific research, and holography. Laser cutting machine is often used in marking or engraving wood, glass, acrylic, rubber, ceramics, coated metals and marble. Laser cutting machine has greater advantages compared to the traditional method for cutting the material. It produces better cut quality of material. The project is to examine the effects of laser cutting of acrylic material with the use of different power levels and constant feed rate. The effects on both parameters, which are striation frequency and the size of HAZ, are analyzed. Manual analysis was used to develop graphs that describe the effects of power on laser cut quality. The suitable desired power level to get the optimum cut quality of acrylic is 22.5 watts at feed rate 1800 μs. For optimum cut quality, striation frequency and size of HAZ parameters are kept at minimum levels. Increasing power leads to the decrease of striation frequency. The size of HAZ increases when there is an increase in power. Power laser produces small effects on the striation frequency and size of HAZ. Study and analyze the other parameters or factors that affect the cut quality of acrylic should be consider for the future research.